Translating the Diabetes Prevention Program in Native Hawaiian and Pacific Islander communities: the PILI ‘Ohana Project - Kaholokula, J K (Springer US, 2013)
Native Hawaiians/Pacific Islanders experience a high prevalence of overweight/obesity. The Diabetes Prevention Program Lifestyle Intervention (DPP-LI) was translated into a 3-month community-based intervention to benefit these populations. The weight loss and other clinical and behavioral outcomes of the translated DPP-LI and the socio-demographic, behavioral, and biological factors associated with the weight loss were examined. A total of 239 Native Hawaiian/Pacific Islander adults completed the translated DPP-LI through four community-based organizations (CBOs). Changes from pre- to post-intervention assessments in weight, blood pressure, physical functioning, exercise frequency, and fat in diet were measured. Significant improvements on all variables were found, with differences observed across the four CBOs. CBOs with predominately Native Hawaiian and ethnically homogenous intervention groups had greater weight loss. General linear modeling indicated that larger baseline weight and CBO predicted weight loss. The translated DPP-LI can be effective for Native Hawaiians/Pacific Islanders, especially when socio-cultural, socio-economic, and CBO-related contextual factors are taken into account.